Siyaq Al-Hijrah ‘inda Ibn Athiyah fi sKitab al-Muharrar al-Wajiz fi al-Tafsir al-Kitab al-‘Aziz - Siti Madinatul Munawwaroh; Rochmad (Studia Quranika, 2021)
Hijrah is defined as an integral part of a Muslim's devotion to Allah SWT as well as a representation of the form of faith. This study aimed to investigate the meaning of Hijrah viewed from Muharrir al-Wajiz interpretations by Ibn 'Atiyah. Hijrah is divided into hijrah hissiyyah and maknawiyah. Ibn 'Atiyah also discussed the meaning of hijrah in the interpretation. How is the interpretation of hijrah according Ibn Atiyah's perspective? From the studies conducted, the author concludes that Ibn 'Atiyah interprets hijrah by observing at the dzahir verse which usually uses gramatical studies, and Asbabun-nuzul without looking at the meaning of the sign or the mind. Hijrah in a Makiyyah letter means moving to Habasyah, the hijrah of prophets Ibrahim and Luth and other meanings that indicate the occurrence before the Prophet's migration to Medina. While the migration in the madaniyah letter, Ibn Atiyah has similarities with other commentators who interpret hijrah as Hissiyyah, He also interpret it as hijrah maknawiyah, its mean moving to Allah and His Messenger, by obeying and leaving what was forbidden by Him, even though the hijrah has stopped after Fathu Makkah, but maknawiyah hijrah is needed for everyone